IMPLEMENTASI KARAKTER ISLAMI DI DESA NAGORI KEBUN SAYUR MELALUI EKSISTENSI PENGAJARAN DAN PERLOMBAAN QUR’AN DAN ADZAN - Zulham; Nabila Zahra; Nafisah Hidayah; Eliva Azzahra Harahap (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community service is an activity organized by the campus to implement the knowledge acquired by students, especially the knowledge acquired during their studies at the campus. In this context, this positive activity aims to directly educate students to engage with the community and develop Islamic moral values in the area. Nagori Kebun Sayur Village, Sidamanik District, Simalungun Regency, North Sumatra, has a population of 1,148. The program implemented was to implement Islamic character through teaching and competitions on the Qur'an and Adhan as a strategic effort to build a young generation with noble character and based on Islamic values. This community service activity was carried out using a qualitative descriptive method with the aim of illustrating and describing the implementation of Islamic character through Islamic teaching and competitions held over a period of 14 days, with children as the main focus of this program. They were taught how to read the Qur'an properly and correctly and were guided using the talaqqi method (reading in front of the teacher and then being corrected) and the tikrar method (repeating the reading together), while the teaching of the adhan was carried out using the direct practice method.